Variation of biomass carbon stock within agroforestry systems in the Senegalese groundnut basin - Mariama Sambou; Brahima Koné; Simon Sambou; Fatimata Niang; Seyni Sane; Malainy Diatta; Hyacinthe Sambou; Assane Goudiaby; Cheikh Mbow; Bienvenu Sambou (Discover Sustainability, 2024)
Abstract Agroforestry plays a pivotal role in mitigating greenhouse gas (GHG) emissions and addressing the challenges posed by climate change. While carbon sequestration efforts have primarily centred on forests, it is imperative to acknowledge the contribution that non-forest ecosystems, such as agroforestry, can offer. This study investigated the influence of agroforestry systems on the variation of biomass carbon stocks in the Sahelo-Sudanian and Sudanian regions of the Senegalese Groundnut basin. Three primary agroforestry systems were studied: silvopastoral, agrisilvicultural, and agrosilvopastoral. Forty-six (46) 100 m × 100 m plots were sampled, within which 1 × 1 m2 subplots were used to sample understory biomass across three agroforestry systems in the two climatic zones. Analysis of variance was performed to assess the influence of agroforestry systems and climatic zones on biomass carbon stocks. The findings showed that in the Sahelo-Sudanian region, the agrisilvicultural system exhibited the highest AGC + BGC stocks, averaging 43.42 ± 21.61 tCha−1. In contrast, the silvopastoral system showed significantly higher AGC + BGC stocks, which amounted to 36.33 ± 12.27 tCha−1 in the Sudanian region. On the other hand, understory carbon stocks were significantly higher (p < 0.01) in the agrisilvicultural and agrosilvopastoral systems than in the silvopastoral system in both climatic zones. Agroforestry systems had a significant effect on AGC + BGC stocks within climatic zones. Nevertheless, the effect was less pronounced when comparing across climatic regions. These results underscore the importance of specific land management practices interacting with local climatic conditions to influence AGC + BGC stocks. Therefore, policy makers should carefully consider the interaction of these factors when implementing carbon management practices and planning mitigation strategies in West Africa.